2008
DOI: 10.1073/pnas.0802331105
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the infectious dose ofLeishmania majortransmitted to the skin by single sand flies

Abstract: Leishmaniasis is transmitted between mammalian hosts by the bites of bloodsucking vector sand flies. The dose of parasites transmitted to the mammalian host has never been directly determined. We developed a real-time PCR-based method to determine the number of Leishmania major parasites inoculated into the ears of living mice during feeding by individual infected flies (Phlebotomus duboscqi). The number of parasites transmitted varied over a wide range in the 58 ears in which Leishmania were detected and demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
199
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(213 citation statements)
references
References 24 publications
11
199
1
2
Order By: Relevance
“…Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6). We and others have demonstrated that the relative differences in parasite load or lesion size following inoculation at different sites or with different doses of parasites can change depending on the time of analysis (1,3,7,36,48). For example, while we observed earlier control of parasite numbers in the ear than in the footpad, likely due to the earlier onset of adaptive immunity as shown here, a 10-fold-higher parasite load was maintained in the ear during chronic infection (3).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6). We and others have demonstrated that the relative differences in parasite load or lesion size following inoculation at different sites or with different doses of parasites can change depending on the time of analysis (1,3,7,36,48). For example, while we observed earlier control of parasite numbers in the ear than in the footpad, likely due to the earlier onset of adaptive immunity as shown here, a 10-fold-higher parasite load was maintained in the ear during chronic infection (3).…”
Section: Discussionmentioning
confidence: 66%
“…Here we demonstrate that even before different antigen-presenting cells begin to prime adaptive immunity, the site of inoculation immediately influences the effective dose of L. major parasites that establishes infection. The parasite dose has far-reaching implications for Leishmania infections, including the nature of the adaptive immune response, and is likely one of the most important variables in determining the kinetics and outcome of infection (6,36,(44)(45)(46)(47)(48)). Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parasite: Although the dose of Leishmania promastigotes delivered by the sand fly vector to the skin of mammalian host has never been directly determined, using a real time-PCR approach it has been possible to reveal a remarkable range of 10 to 100,000 in the dose of parasites transmitted to mice exposed to a single infected sand fly 15 . More recently, another study determined infection parameters in the sand fly vector that predict transmission of L. (L.) major: it was estimated in the range of 10 3 to 10 6 total parasites per fly 34 .…”
Section: Animalsmentioning
confidence: 99%
“…The existence of two distinct patient profi les (classic and severe) might be a consequence of several factors such as the infective strength level 11 , host immunosuppression 8,12,13 , and the genetic background of the host 14,15 , or it might be genetically determined by parasitic virulence factors 16 . The identifi cation of genetic changes in the pathogenic target genes is a starting point in the search for virulence factors 17 .…”
Section: Introductionmentioning
confidence: 99%